2007
DOI: 10.1080/00103620601093611
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Phosphorus Sources for Grain Amaranth Production

Abstract: Phosphorus (P) is expensive to the sub-Saharan African resource-poor farmers; therefore, there is a need for investigation of locally available alternative P sources to enhance farmers' productivity. Optimum P rate was determined during the early and late rains of 1999. Using the optimum P rate, influences of three P sources ogun rock phosphate (ORP), sokoto rock phosphate (SRP), single super phosphate (SSP) and a control were evaluated on amaranth varieties in 2000 at the vegetable research plots of the Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
(39 reference statements)
2
3
1
5
Order By: Relevance
“…The fertilization formula was 80-20-00 kg ha -1 of N-P-K plus one ton of compost ha -1 with the highest grain yield in both variables (Figure 3 and 4). In relation to the doses of N, these results are similar to those reported by Ojo et al (2007) who mention that under optimal conditions the optimum N doses should be in the range of 60 to 80 kg ha -1 . However, Myers (1998), in an experiment conducted in Missouri, USA, evaluated doses of 0 to 180 kg N ha -1 and found a higher yield at the highest dose.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The fertilization formula was 80-20-00 kg ha -1 of N-P-K plus one ton of compost ha -1 with the highest grain yield in both variables (Figure 3 and 4). In relation to the doses of N, these results are similar to those reported by Ojo et al (2007) who mention that under optimal conditions the optimum N doses should be in the range of 60 to 80 kg ha -1 . However, Myers (1998), in an experiment conducted in Missouri, USA, evaluated doses of 0 to 180 kg N ha -1 and found a higher yield at the highest dose.…”
Section: Resultssupporting
confidence: 80%
“…Siendo la fórmula de fertilización 80-20-00 kg ha -1 de N-P-K más una tonelada de composta ha -1 con la que se obtuvo el mayor rendimiento de grano, en ambas variables (Figura 3 y 4). En relación a las dosis de N, estos resultados son similares a los reportados por Ojo et al (2007) quienes mencionan que en condiciones de temporal las dosis de N óptimas deberán estar en el rango de entre 60 y 80 kg ha -1 . No obstante, Myers (1998) en un experimento realizado en Missouri, Estados Unidos de América evaluó dosis de 0 a 180 kg N ha -1 y encontró mayor rendimiento con la dosis más alta.…”
Section: Resultsunclassified
“…Phosphorus is found at low concentrations in the soil solution, causing limitation of biomass productivity in tropical soils [15]. In the literature, the reported cases where the effect of P doses on amaranth culture [17] and [18] were studied under field conditions. Therefore, the information on residual P, after soybean cultivation, is not sufficient for a correct positioning on its management in the amaranth culture in succession, when aiming at economic yield.…”
Section: Introductionmentioning
confidence: 99%
“…BRS Alegria seeded in succession to soybean in Goiás, obtained 2,000 kg ha -1 of grain yield with application of 60 and 80 kg ha -1 of P 2 O 5 and K 2 O, respectively. In a study conducted in Malaysia, [17] in Malaysia, they concluded, for the purpose of fertilizer recommendation, that 50 kg of P ha -1 (114.57 kg.ha -1 of P 2 O 5 ) was the most adequate for the production of leaves and grains of amaranth.…”
mentioning
confidence: 99%
“…Although environmental conditions are known to influence crop growth and global climatic changes are assumed to worsen cropping conditions in sub-Saharan African with dry spells becoming more frequent, only one paper published recently deals with the impact of soil moisture stress on AIVs (Olufolaji and Ojo, 2010). A few others focused on nutrient management (Ojo et al, 2007). It can be concluded that most aspects of the cultivation or cropping systems of AIVs are heavily under emphasized.…”
Section: Introductionmentioning
confidence: 99%